Successful laparoscopic living donor nephrectomy: first experience in Lithuania - Laučytė-Cibulskienė, Agnė; Miglinas, Marius; Želvys, Arūnas; Čekauskas, Albertas (Acta medica Lituanica, 2019)
Background. The aim of this paper is to share the initial results of LLDN in high-volume university centre that is performing laparoscopic nephrectomies for other indications. Materials and methods. During 2017, four LLDNs were performed. The transperitoneal approach was used in all cases and the kidney was removed using a suprapubic incision. All donors and recipients were prospectively analysed within six-month follow-up. The patients’ clinical, laboratory, and operation-related data were collected from direct interviews with them and from medical records. All patients signed written informed consent. Results. One male and three females donated their left kidneys by using the LLDN technique. The mean age was 58 ± 9 years; two of them with a history of previous cholecystectomy. All donated kidneys had a single renal artery and renal vein. Pre-operative average eGFR was 94.2 ± 7.1 ml/min/1.73 m2, immediately after LLDN 57.5 ± 10.3 ml/min/1.73 m2, after one month 56.0 ± 9.1 ml/min/1.73 m2. There were no intraoperative complications; surgery duration was 223.75 ± 21.74 min, the cold ischemia time was 77.5 ± 28.77 min, and the warm ischemia time 6.37 ± 3.14 min. There was one postoperative donor complication, one case of acute kidney injury, and one case of prolonged postoperative abdominal pain. The only recipient complication was one case of acute kidney rejection; there were no cases of delayed graft function. Conclusions. Our initial experience confirms that LLDN is an approach that is easy to learn, especially in a high-volume university hospital with expertise in performing laparoscopic nephrectomies for other indications.
Keywords: laparoscopic nephrectomy; living donor; kidney transplantation; transperitoneal approach